Upaya Mengurangi Perilaku Blindism melalui Token Economy pada Anak Tunanetra di SLB Negeri 2 Padang - Fitra, Bunga Rahmah; Sopandi, Asep Ahmad (Jurnal Penelitian Pendidikan Khusus, 2024)
This research aims to prove whether blindism behavior pressing on the eyes of blind children at SLB Negeri 2 Padang can be reduced by using a token economy. In this study, an A-B-A design single subject experimental research (SSR) was employed. Tables and graphs are used to present the data analysis findings, which take the form of descriptive statistics. Analysis was done using 16 observation data, and the baseline phase findings were 30, 29, 29, and 29 (A1). The following outcomes were attained in the intervention phase (B): 28, 27, 25, 24, 22, 21, 21, and 21. Additionally, the outcomes in the second baseline phase (A2) were 20, 20, 20, and 20. In light of data analysis, the outcomes Research indicates that the blindness behavior of suppressing the eyes of blind children during learning is reduced after using a token economy.